Constitutional promises of indigenous recognition: Canada, Vanuatu and the challenges of pluralism. (December 2019) - Corrin, Jennifer; Young, Simon
The Constitutions of Canada and Vanuatu commit to recognition of 'Aboriginal rights' and 'customary laws', respectively. The translation of these aspirations has led the courts deep into the challenges of pluralism, magnified here by the weight of colonialism and constitutional context. This article explores the progress in these two contrasting countries to provide a broader view of the undertaking. It is argued that the persistence of visible problems reveals more fundamental difficulties and that the collaboration essential to the task of 'recognition'—and to shoring up Western legal systems in the modern reality—must begin earlier and run deeper.